Why the Simple View of Reading Is Not Simplistic: Unpacking Component Skills of Reading Using a Direct and Indirect Effect Model of Reading (DIER) - Kim, Young-Suk Grace (Scientific studies of reading, 2017)
Pathways of relations of language, cognitive, and literacy skills (i.e., working memory, vocabulary, grammatical knowledge, inference, comprehension monitoring, word reading, and listening comprehension) to reading comprehension were examined by comparing four variations of direct and indirect effects model of reading. Results from 350 English-speaking second graders revealed that language and cognitive component skills had direct and indirect relations to listening comprehension, explaining 86% of variance. Word reading and listening comprehension completely mediated the relations of language and cognitive component skills to reading comprehension and explained virtually all the variance in reading comprehension. Total effects of component skills varied from small to substantial. The findings support the direct and indirect effects model of reading model and indicate that word reading and listening comprehension are upper-level skills that are built on multiple language and cognitive component skills, which have direct and indirect relations among themselves. The results underscore the importance of understanding nature of relations.